COVID-19 and Cancer Care in Indonesia: What we have done in Dharmais Cancer Center Hospital - Hendi Setiadi; Fifi Dwijayanti; Martya Rahmaniati Makful (Indonesian Journal of Cancer, 2020)
At the end of 2019, the novel coronavirus (CoV) of severe acute respiratory syndrome (SARS), named SARS- CoV-2 was approved as a microbial agent that causes viral pneumonia in patients who are linked epidemiologically to the seafood market in Wuhan (Wuhan) Hubei province, China [1]. The World Health Organization (WHO) stated the coronavirus or COVID-19 as a pandemic because it has spread globally in the world since March 11, 2020 [2]. There have been more than 8 million cases reported with more than 450 thousand deaths around the world until June 19, 2020 [3]. Indonesia reported the first cases of COVID-19 in early March 2020 and currently 43,803 cases with 2,373 deaths [4]. Indonesia has the highest cases of COVID-19 in Southeast Asia [5]. WHO stated that according to the current evidence, coronavirus is transmitted among people through respiratory droplets and contact routes [6-8]. Droplet transmission is different from airborne disease. Droplet transmission occurs when a person closely contacted (within 1 m) with someone who has respiratory symptoms (e.g. coughing or sneezing,) and was therefore at risk of having his/her mucosae (mouth and nose) or conjunctiva (eyes) exposed to potentially infective respiratory droplets. Droplet transmission may also occur through fomites in the immediate environment around the infected person [9]. Increasing cases occur continuously become alert for our institution as health care providers.